KERAJINAN COR LOGAM ALUMINIUM SEGOROYOSO PLERET BANTUL, DAERAH ISTIMEWA YOGYAKARTA - Timbul Raharjo; Joko Subiharto (Corak : Jurnal Seni Kriya, 2017)
The cast aluminum products at Karanggayam, Segoroyoso, Pleret, Bantul is suffering from quality stagnation. They are limited to manufacturing "Vandels", Logos, and Souvenirs as their main products. These products will then be sold to some business around Yogyakarta. The method of manufacturing is still very traditional, Dry casting the aluminum in soft sand. They haven't been able to produce products with certain artistic specifications to supply the global market demand. Thus the need to increase the quality of post-producing techniques like polishing and lathe work is required. These can be achieved by developing the industry in various aspect including but not limited to creation, production, distribution, and management. The 2 targets of this development are 2 home industries: "Habibi Cor" and "Abu Cor". By working on existing technique and skills, compounded by new designs and the application of a polishing machine and a Lathe machine these 2 home industries can be further improved.The goal of this Program to develop the cast aluminum industry is to accelerate the industry by adding polishing and lathe work, as well as adding a new design like accessories, sculpture, and wall decoration and to increase export by matching the current world trend. After the application of the new technologies and methods, an increase in export is to be expected. which in turn will increase the economic condition of the craftsmen. The methods used are for example: explaining about the uses of this project by socializing the goals, motivation, and the form of the activities itself. Various workshop and guidance programs to give the methods of developing new design, increasing product quality by polishing, and expanding the knowledge about management especially around accounting, producing, and marketing. Key Words: Craft, Cast Aluminum, Segoroyoso